Molecular dynamics of carrageenan composites reinforced with Cloisite Na+ montmorillonite nanoclay - Sanchis M.J. (2017)
This work was supported by the Dirección General de Ciencia y Tecnología (DGCYT) [MAT2015-63955-R]; the Vice-Rectorate for Research of the Pontificia Universidad Católica del Perú and the National Council of Science, Technology and Technological Innovation of Peru (CONCYTEC/FONDECYT).